GEOCHEMICAL AND PETROPHYSICAL ASSESSMENT OF LITHOLOGICAL VARIABILITY AND RESERVOIR PROPERTIES OF WELLS CORE: RUNOVSHCHYNA OIL AND GAS FIELD OF THE DNIPRO-DONETSK BASIN AS AN EXAMPLE (PRELIMINARY RESULTS) - VYZHVA, Serhii; HAFYCH, Ivan; GOZHYK, Andrii; SHABATURA, Oleksandr; SHNYUKOV, Sergiy (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. A comprehensive petrophysical and geochemical study of a representative series of core samples (n=79) was performed for real well sections of the Runovshchyna oil and gas area of the Dnieper-Donets Basin containing productive horizons. The aim of the work was to test the possibility of full integration of geochemical methods with geophysical well logging data to improve the efficiency of data interpretation. Methods. A set of petrophysical parameters (including porosity and permeability of rocks), as well as the content of major and trace elements (WDXRF, EDXRF) were determined for all core samples after their uniform preparation and preliminary petrographic study. Obtained analytical results were used to create a combined petrophysical and geochemical data bank. Results. The created database allowed to calculate the contents of quartz (Qtz), clays (CLAY), carbonates (CARB) and organic matter (ORG) in rocks based on the content of the main elements and on the previously proposed 4-component lithological model. It also allowed to characterize the quantitative lithology of the section within the studied intervals and to show the possibility of identifying local geochemical sulfur anomalies that are indicators of oil-bearing intervals. It was proposed to establish a stable correlation between instrumentally determined porosity and permeability and the content of model components Qtz, CLAY and the coefficient (K2O+Na2O+Al2O3+TiO2)/LOI and to confirm the possibility of using neural networks to interpret the data. Conclusions. There is effectiveness of geochemical methods (elemental geochemistry) in the variants of studying the core and cuttings of wells ("geochemical log") for confident (without information losses and distortions) distribution of the results of direct "point" study of filtration and capacitance parameters of core samples in the intervals of its selection to the entire well section for full integration with the data of the well logging, achievement of the most unambiguous quantitative interpretation of all data and the needs of geosteering during drilling. The expediency of using neural networks to improve the accuracy of determining filtration and capacitance properties using petrophysical and geochemical data is confirmed.